COMPETITIVENESS OF RAIL FREIGHT CORRIDORS – CASE STUDY: CORRIDORS X AND IV - Stanojević, Miloš; Bošković, Branislav; Bugarinović, Mirjana (Horizons - International Scientific Journal, 2018)
After almost 30 years since the first declaration of corridor network of Europe and the same amount of time spent on investments in its development with goal of creating single european transport market, it seems like the era of competitiveness of some of the corridors has begun. The term of corridor competitveness, its significance, factors of competitiveness and comparative analisys of factors for TEN-T Corridors X and IV have been reviewed in this paper. Also, paper reviews methods of evaluation of corridor competitiveness which have been used in other author’s work, followed by the method of comparative analisys. As main factors of competitiveness of these two corridors in this moment, this paper specialy marks the length of corridor, travel time - commercial speed of the train, waiting time at border crossings, level of access charges and usage of corridor capacity.